Polystyrene Nanoplastics Elicit Multiple Responses in Immune Cells of the Eisenia fetida (Savigny, 1826) - Huijian Shi; Yaoyue Wang; Xiangxiang Li; Xiaoyang Wang; Yuntao Qi; Shaoyang Hu; Rutao Liu (Toxics)
The improper disposal of plastic products/wastes can lead to the release of nanoplastics (NPs) into environmental media, especially soil. Nevertheless, their toxicity mechanisms in soil invertebrates remain unclear. This study investigated the impact of polystyrene NPs on Eisenia fetida (Savigny, 1826) immune cells, focusing on oxidative stress, immune responses, apoptosis, and necrosis. Results showed that 100 nm NPs were internalized into the cells, causing cytotoxicity. NPs were observed to inhibit cell viability by increasing reactive oxygen species, decreasing the levels of antioxidants (e.g., superoxide dismutase, catalase, and glutathione), and inducing lipid peroxidation and DNA oxidation. Additionally, assays on neutral red retention time, lysozyme activity, and Ca2⁺ levels demonstrated that NPs resulted in a loss of lysosomal membrane stability and a reduction in immune resistance. The depolarization of the mitochondrial membrane potential and the results of the apoptosis assays confirmed that the NPs induced the onset of early apoptosis. The difficulty of the NP in causing cell death by disrupting the plasma membrane was demonstrated by the results of the lactate dehydrogenase release assays in relation to cell necrosis. This research provides cellular-level insights into the ecological risks of NP exposure on soil fauna.